2020
DOI: 10.1155/2020/7897268
|View full text |Cite
|
Sign up to set email alerts
|

Brief Acceptance and Commitment Therapy for Fibromyalgia: Feasibility and Effectiveness of a Replicated Single-Case Design

Abstract: Objective. Overall, the literature on the effectiveness of psychological treatments in general and those for fibromyalgia in particular has been dominated by research designs that focus on large groups and explore changes on average, so the treatment impact at the individual level remains unclear. In this quasi-experimental, replicated single-case design, we will test the feasibility and effectiveness of a brief acceptance and committed therapy intervention using ecological momentary assessment supported by te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 70 publications
0
20
1
Order By: Relevance
“…The interventions consisted of 10 individual and inperson sessions in each phase (phase A and phase B) and weekly periodicity, corresponding to the number of sessions tested in this target population (Äsenlöf et al, 2005;Gómez-Pérez et al, 2020;Lundervold et al, 2006;Lundervold et al, 2008). The sessions were conducted by an experienced psychologist in the field.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interventions consisted of 10 individual and inperson sessions in each phase (phase A and phase B) and weekly periodicity, corresponding to the number of sessions tested in this target population (Äsenlöf et al, 2005;Gómez-Pérez et al, 2020;Lundervold et al, 2006;Lundervold et al, 2008). The sessions were conducted by an experienced psychologist in the field.…”
Section: Methodsmentioning
confidence: 99%
“…In a search in the databases of Portal Capes (Index Psi, Pepsic, Scielo, and BVS), using the keywords "single-case AND pain AND behavior analysis," it was possible to verify that only a few behavioral intervention studies using single-case designs were found for people with chronic pain, including FM (Äsenlöf, Denison, & Lindberg, 2005;Gómez-Pérez, García-Palacios, Castilla, Zaragozá, & Suso-Ribera, 2020;Lundervold, Talley, & Buermann, 2006;Lundervold, Talley, & Buermann, 2008). These studies measured, besides the intensity and inability of pain, variables such as anxiety and depression (Gómez-Pérez et al, 2020;Lundervold et al, 2006;Lundervold et al, 2008) and coping with pain strategies (Äsenlöf et al, 2005). Until the present moment, none of the studies proposed the use of sleep and insomnia measures.…”
Section: Introductionmentioning
confidence: 99%
“…They were all published between 2012 and 2020. While 5 studies were uncontrolled clinical trials [ 91 , 92 , 93 , 94 , 95 ], the remaining 16 did have one or more control group/s. Ten studies were performed in Europe (Sweden, United Kingdom, Spain, Denmark, Italy, Greece and Cyprus) [ 96 , 97 , 98 , 99 , 100 ], five in the USA [ 101 , 102 , 103 , 104 , 105 ], four in Iran [ 106 , 107 , 108 , 109 ], one in Canada [ 110 ], and one in Japan [ 111 ].…”
Section: Resultsmentioning
confidence: 99%
“…The 21 selected studies on ACT for CPSS [ 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 ] included 1090 individuals who completed the pre/post-test phases (average of 52 subjects per study; range: 7 to 141 participants). Approximately half of the participants were included in the ACT group ( n = 601) and the others were included in control groups ( n = 487).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation